El valor de la calidad educativa en la práctica pedagógica (Educational Perspectives Magazine (REPED), 2023)
This paper aims to share and reflect the educational experience observed in Kindergarten Andalué, educational unit based on an observed activity of our training, what the particular experience is that the practice of the establishment is based on the Montessori method, which may actually not a worthwhile feature rescued. However, the exception is the origin and location of the garden. The construction of this space stems from a project of university students and the commitment of people from the municipality of Cerro Navia. The Garden community of Andalué children, belongsto the Educational Corporation Tricahue, nonprofit organization that brings together people from different worlds: the inhabitants of the world professional colleagues and friends of Europe. All by one goal in common: “Educating for Ufe”.